Determinan Kegagalan Kognitif Perawat di Tempat Kerja - Nugraheni, Intan Setya; Budiadi, Nang Among; Sugiyarmasto, Sugiyarmasto (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Cognitive failure is a problem in carrying out daily activities of nurses in hospitals, because it can reduce nurse performance and productivity. Aims: This research was conducted to predict stress factors, poor sleep quality, secondary trauma and work-related fatigue on nurses' cognitive failure in the workplace. Methods: This research is quantitative research with a survey design. Data was collected using a questionnaire from respondents aimed at nurses at the hospital. The sampling technique uses purpose sampling technique and the sample size is 202. This research uses SEM (Structural Equation Modeling) analysis. Results: Based on the analysis of the results, the research results show: stress has a significant effect on cognitive failure, poor sleep quality has a significant effect on cognitive failure, secondary trauma has a significant effect on cognitive failure and work-related fatigue has an insignificant effect on cognitive failure. Conclusion: Nurses' cognitive failure is caused by stress factors, poor sleep quality and secondary trauma.